2010
DOI: 10.1186/1471-2334-10-298
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity and safety of a reduced PRP-content DTPw-HBV/Hib vaccine when administered according to the accelerated EPI schedule

Abstract: BackgroundCombination vaccines improve coverage, compliance and effectively introduce new antigens to mass vaccination programmes. This was a phase III, observer-blind, randomized study of GSK Biologicals diphtheria-tetanus-whole cell pertussis vaccine combined with hepatitis B and Haemophilus influenzae type b vaccines, containing a reduced amount of polyribosyl-ribitol-phosphate (PRP) and a DTPw component manufactured at a different site (DTPw-HBV/Hib2.5 [Kft]). The primary aim of this study was to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Antibody concentrations against the PRP, tetanus and diphtheria antigens were higher when PHiD-CV was co-administered, presumably due to enhancement of these immune responses by the tetanus toxoid and diphtheria toxoid carrier proteins used for serotypes 18C and 19F, respectively, in PHiD-CV [28]. High antibody GMCs and seroprotection rates were however observed for these antigens in both groups, including the PRP antigen, confirming the good immunogenicity of a reduced PRP content Hib vaccine (2.5 μg of PRP) compared to the more usual 10 μg PRP vaccines [41-45]. …”
Section: Discussionmentioning
confidence: 94%
“…Antibody concentrations against the PRP, tetanus and diphtheria antigens were higher when PHiD-CV was co-administered, presumably due to enhancement of these immune responses by the tetanus toxoid and diphtheria toxoid carrier proteins used for serotypes 18C and 19F, respectively, in PHiD-CV [28]. High antibody GMCs and seroprotection rates were however observed for these antigens in both groups, including the PRP antigen, confirming the good immunogenicity of a reduced PRP content Hib vaccine (2.5 μg of PRP) compared to the more usual 10 μg PRP vaccines [41-45]. …”
Section: Discussionmentioning
confidence: 94%
“…Safety data from these studies showed pain, swelling and erythema as the most commonly reported solicited local reactions, and most frequently reported solicited systemic reactions were fever and irritability comparable with our observations. [12][13][14][15][16][17] For several decades, inactivated whole-cell pertussis vaccines (wP) have been part of national childhood vaccination programs, dramatically reducing the considerable public health impact of pertussis. 18 In most emerging and developing countries, DTP vaccination in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct comparisons are not possible due to differences in data collection and analysis methods, seroprotection/seroconversion rates and reactogenicity profile were found to be similar to other pentavalent vaccines studied in Indian infants. [12][13][14][15][16][17] This study was designed to assess immunogenicity in terms of accepted seroprotection or seroconversion criteria against all five vaccine antigens one month after the third vaccination, and safety and tolerability after each vaccine dose. The study was conducted according to Good Clinical Practice and in accordance with the Ethical Guidelines for Biomedical Research on Human Subjects and Declaration of Helsinki.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] However, the safety and immunogenicity of two different presentations of Quinvaxem had not been studied to date. In this study, the seroconversion/seroprotection rates were similar in the cPAD and single-dose vial groups.…”
Section: Discussionmentioning
confidence: 97%
“…Frequent, but usually mild adverse reactions, and a fear of rare but serious acute or chronic neurological events associated with wP vaccination, prompted the development of a new generation of pertussis vaccines, the aP vaccines, which are believed to have fewer such reactions than wP vaccines. 27,32 However, evidence suggests that licensed aP vaccines have lower initial efficacy, faster waning of immunity, and possibly a reduced impact on transmission compared with current internationally available wP vaccines. 33,34 Mathematical modeling studies and baboon models support the hypothesis that transition from wP to shorter duration of protection aP may be associated with disease resurgence.…”
Section: Discussionmentioning
confidence: 99%